Uji reliabilitas try out ipa siswa kelas vi Sekolah Dasar Negeri 028 Srikayangan Kecamatan pujud tahun pelajaran 2013/2014 - Mawaty Simamora, Dewi Mawaty Simamora Dewi; Yusuf, Sardi Yusuf Sardi; Yakub, Elni Yakub Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractThe problem of this research is ow is the degree of try out reliability essay of science grad VI which made by the essay maker team in year 2013/2014. The purpose this research is two know about the degree of try out reliability essay of science grade VI which made by the essay maker team in year 2014/2014. While the research benefit is as the comparison material for the science teachers and to help the student in understanding the problems which happen in their lifes, and can increase the student perception and knowledge, also to increase the student scientific. The population in this research all of the student of SD Negeri 028 Srikayangan grade VI and there are 36 student which made a sample. The sample whichis use in this research is total sampling, and to take thesample is use. The probability sampling or random sampling. This research used the Split-Halves correlation methode which had the correlation with Product Moment, with Searman Brown, and then the result is compared with the estimate KR 20 formula. To data which is need to be analysis is the data about : the result of the science Try Out of SD Negeri 028 Srikayangan grade VI Kecamatan Pujud in year 2013/2014. The analysis data method : the data which will be analyzed divited in to two groups which is the group of even numbers essay and add numbers essay, with the correlation formula r Product Moment, Spearman Brown, and r estimate KR 20. The conclusion : the reability test with the correlation formula have mark r = 0, 10 correlation cattegori is in the lower level, the reliability test with Spearman Brown formula have mark r = 0, 18 correlatian cattegori is in the lower level, and the reliability test with KR 20 formula have mark r = 0, 55 cattegori is in the middle level. Keywords : Validitas and Reliabilitas of aclievement